Cover Jurnal Sospol Vol. 2, No. 1, Juli - Desember 2016 - Jurnal Sospol, Cover (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2016)
Cover Jurnal Sospol Vol. 1, No. 1, Juli - Desember 2016